A meta-analysis of the effectiveness of gratitude interventions on well-being across cultures - Hyewon Choi; Youngjae Cha; Michael E. McCullough; Nicholas A. Coles; Shigehiro Oishi (Proceedings of the National Academy of Sciences, 2025)
Gratitude practice is a popular strategy for promoting happiness worldwide. However, is it equally effective for people from different cultural backgrounds? To answer this question, we conducted a preregistered meta-analysis on the effectiveness of gratitude interventions on well-being across cultures. Using data from 145 papers, 163 samples, 727 effect sizes, and 24,804 participants from 28 countries, we found that gratitude interventions led to small overall increases in well-being, Hedges’ g = 0.19, 95% CI [0.15, 0.22]. Moderation analyses revealed significant between-country differences in the effects of gratitude interventions. However, we found no significant evidence of moderators explaining such cross-cultural variability, highlighting the need for more primary research in this domain. Subsequent analyses indicated that three methodological characteristics moderated the effects: well-being outcomes, intervention types, and randomization. The effectiveness of gratitude interventions was greater when well-being outcomes were measured as positive affect, when multiple types of gratitude interventions were combined, and when randomized controlled trials were employed. Overall, the results appeared to be robust against publication bias and the presence of influential cases. These findings contribute to a deeper understanding of the effectiveness of gratitude interventions on well-being across cultural contexts and methodological characteristics.